Follicle‐stimulating hormone effectiveness in male idiopathic infertility: What happens in daily practice?. (2nd December 2022) - Romeo, Marilina; Spaggiari, Giorgia; Nuzzo, Federico; Granata, Antonio R. M.; Simoni, Manuela; Santi, Daniele
Abstract: Objectives: To assess the effectiveness of follicle‐stimulating hormone (FSH) administration in male idiopathic infertility in a clinical setting. Methods: A retrospective real‐world study was carried out, including all consecutive FSH‐treated infertile men attending the Andrology Unit of Modena (Italy) from June 2015 to May 2022. Medical history, physical and andrological examinations, hormonal and seminal parameters, therapeutic management and pregnancy data were collected. The primary endpoint was the number of pregnancies obtained after FSH administration, whereas semen parameters change was the secondary outcome. Results: A total of 194 of 362 (53.6%) infertile men, eligible according to the Italian Health System regulations, were treated with FSH (mean age 37.9 ± 6.1 years). Following FSH administration (mean therapy duration 9.1 ± 7.1 months), 43 pregnancies were recorded (27.6%), of which 22 occurred naturally and 21 after assisted reproduction. A significant increase in sperm concentration (9.9 ± 12.2 vs. 18.9 ± 38.9 million/mL, p = 0.045) was detected after treatment, together with a significant increase in normozoospermia (from 1.0% to 5.1%, p = .044) and a reduction in azoospermia rate (from 9.8% to 7%, p = 0.044). Dividing the cohort in FSH‐responders and non‐responders, in terms of pregnancy achieved, higher sperm concentrations (15.7 ± 26.6 vs. 22.2 ± 25.7 million/mL, p = 0.033) and progressive sperm motility (18.0 ± 18.2 vs. 27.3 ± 11.3, p = 0.044) were found in pregnancy group. Conclusion: Our experience suggests that FSH, empirically administered to men with idiopathic infertility, leads to pregnancy in one out of four patients and increases sperm concentration. Although the expected limits because of a real‐world data study, the number of FSH‐treated patients required to achieve one pregnancy seems to be lower in clinical setting if compared to previously published data.